PEMANFAATAN TEH KOMBUCHA SEBAGAI OBAT HIPERURISEMIA MELALUI PENGHAMBATAN AKTIFITAS XANTIN OKSIDASE PADA Rattus norvegicus - Dewa Ayu Windu Manik Anandagiri; I. B. Putra Manuaba; Ni G. A. M. Dwi Adhi Suastuti (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2014)
The formation of high levels of uric acid and problems of its excretion from the body can lead to hyperuricemia. This study serves to examine the kombucha tea as a hyperuricemia drug activity through the inhibition of the enzyme xanthine oxidase. Kombucha tea was used with three different variations of fermentation namely: tea A (4 days), tea B (8 days), tea C (12 days), and two variations of the dose, i.e. 10 mL/kg BW and 40 mL/kg BW. This study uses a “posttest only control group” design. A total of 27 Wistar rats (Rattus norvegicus) are grouped into 9 groups, K (negative control), H (control hyperuricemia), A (control allopurinol), P1 (tea A dose of 10 mL/kg BW), P2 (tea A dose 40 mL /kg BW), P3 (tea B dose 10 mL/kg BW), P4 (tea B dose 40mL/kg BW), P5 (tea C dose 10 mL/kg BW), P6 (tea C dose 40 mL/kg BW). The rats were given high feed purine for research, namely chicken liver juice and melinjo so that they contracted the hyperuricemia condition. The high purine feeds were administered on all groups of rats except the negative control group. Experiment was undertaken to compare the effectiveness of allopurinol with kombucha tea. This experiment was done for nine days. On the last day, an analysis of the levels of uric acid and xanthine oxidase activity was undertaken and the data was analyzed using ANOVA. The conclusion was that the biggest decline in drug for the treatment of hyperuricemia was kombucha tea B with the dose of 40 mL/kg BW.